2011
DOI: 10.1002/bip.22009
|View full text |Cite
|
Sign up to set email alerts
|

Binding free energies of inhibitors to iron porphyrin complex as a model for Cytochrome P450

Abstract: The binding free energies of the inhibitor-heme model complexes are calculated using the density functional methods and the implicit solvation models in water, where the 16 structurally diverse compounds with a spectrum of IC(50) values from 0.05 (clotrimazole) to 1000 (piroxicam) μM are chosen as inhibitors for Cytochrome P450 3A4 (CYP3A4). CYP3A4 is the most predominant constituent of the human hepatic CYP enzymes that play a role in metabolizing structurally diverse xenobiotics. The observed free energy cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The binding free energies of 16 structurally diverse CYP3A4 inhibitors to the iron porphyrin model, calculated using DFT and the implicit solvation methods in water, were shown to be a good descriptor in interpreting the CYP3A4-inhibitor interaction [102]. The relative free energies in the gas phase were mainly responsible for the total binding free energies in water, although desolvation could affect the inhibitor affinity.…”
Section: 3 Computational Approachesmentioning
confidence: 99%
“…The binding free energies of 16 structurally diverse CYP3A4 inhibitors to the iron porphyrin model, calculated using DFT and the implicit solvation methods in water, were shown to be a good descriptor in interpreting the CYP3A4-inhibitor interaction [102]. The relative free energies in the gas phase were mainly responsible for the total binding free energies in water, although desolvation could affect the inhibitor affinity.…”
Section: 3 Computational Approachesmentioning
confidence: 99%
“…Finally, it was reported recently that the inhibitor binding to CYP3A4 can be predicted fairly well based on the total binding free energies calculated for the inhibitor-heme model complexes. 67 …”
Section: Computational Studies On Cyp3a4mentioning
confidence: 99%
“…Determination of the CYP3A4 X-ray structures triggered a number of theoretical studies that provided deeper insights into the catalytic mechanism and substrate/inhibitor binding, and made possible a more accurate prediction of small-molecule association to CYP3A4. [59][60][61][62][63][64][65][66][67][68] The first MD simulations were conducted by Park et al 59 to clarify the roles of solvent dynamics and the active site loops in the ligand binding process and heme iron coordination. They showed that the malleability of the F-F′ loop (residues 211-218) defines the broad substrate specificity of CYP3A4, and that its complex with the inhibitor metyrapone is stabilized not only via direct coordination to the heme iron but also through a hydrogen bond between the metyrapone carbonyl oxygen and the Ser119 hydroxyl.…”
Section: Computational Studies On Cyp3a4mentioning
confidence: 99%
“…W ith regard to our article, referenced in the title above, 1 Rydberg has raised two important issues. 2 The first issue is that why only the water-assisted binding of fluconazole to ferric iron was considered in the analysis, although there are two binding modes of fluconazole with the heme iron, that is, the direct and water-assisted bindings, in the Xray structure of CYP121-fluconazole complex.…”
mentioning
confidence: 99%
“…3 As described in the Introduction section of our article, 1 these two binding modes were used as the initial structures for optimization, and only the results for the water-assisted binding were included in the analysis. 1 This is why only the water-assisted binding of fluconazole to heme was considered in the analysis, although this is not explicitly described in our article. However, the former value for the direct binding is much larger compared with the observed value of 26.28 kcal/mol obtained from its IC 50 value.…”
mentioning
confidence: 99%